Walking During Leisure-Time in Relation to Perceived Neighborhoods. (August 2015) - Suminski, Richard R.; Wasserman, Jason A.; Mayfield, Carlene A.; Kheyfets, Arthur; Norman, Jared
Are researchers correct to assume individuals who walk during leisure-time do so mostly in their neighborhood? To address this question, we examined relationships between leisure-time walking and boundaries of participant- and researcher-defined neighborhoods. Door-to-door interviews were completed with 415 adults residing in a Midwestern, U.S. city. Participants self-reported physical activity and drew on a map their perceived neighborhoods and their typical leisure-time walking routes. We found that 134 participants walked in their neighborhoods at least once during the past week on the route they drew. Routes were used for 82.9% of the leisure-time walks and 67.9% of the route was within perceived neighborhood boundaries. Almost all of the routes (98.2%) were within a straight-line 2, 000 m buffer around participants' homes. The present study suggests leisure-time walking is neighborhood-based and certain researcher-defined areas are adequate when exploring this behavior. Route characteristics described in this study may have implications for initiatives promoting neighborhood walking.